1993
DOI: 10.1891/0047-2220.24.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Executives in Fortune 500 Corporations Toward the Employability of Persons with Severe Disabilities: Industrial and Service Corporations

Abstract: Three-hundred-forty-one executives responsible for hiring decisions in Fortune 500 industrial and service corporations returned a mail questionnaire measuring their attitudes toward persons with severe disabilities. Attitudes were favorable to the employability of persons with severe disabilities both in terms of its advantages for the individual with a disability and the lack of disadvantages for others in the work setting. Attitudes were more favorable in industrial than service corporations in the area of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 0 publications
2
24
1
Order By: Relevance
“…Most research indicates that contact and exposure to persons with disabilities has a positive effect on attitudes toward disabled persons (Cook 1978;McFarlin et al 1991;Satcher and Hendren 1991;Levy et al 1992;Levy et al 1993;Nosse 1993;Florian 1978). Research on the contact hypothesis suggests that increased exposure to disabled individuals may give people an opportunity to gather more information and form less stereotyped views of persons with disabilities.…”
Section: Awareness Of Persons With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research indicates that contact and exposure to persons with disabilities has a positive effect on attitudes toward disabled persons (Cook 1978;McFarlin et al 1991;Satcher and Hendren 1991;Levy et al 1992;Levy et al 1993;Nosse 1993;Florian 1978). Research on the contact hypothesis suggests that increased exposure to disabled individuals may give people an opportunity to gather more information and form less stereotyped views of persons with disabilities.…”
Section: Awareness Of Persons With Disabilitiesmentioning
confidence: 99%
“…McFarlin et al (1991) report that executives from companies with "below average" levels of exposure to disabled individuals held significantly less positive attitudes regarding first impressions, rate of advancement and absenteeism rates for disabled individuals than executives for companies with "above average" exposure. Levy et al (1992) report that executives in Fortune 500 corporations who had contact with persons with disabilities in the work context had more positive attitudes toward disabled persons than did executives who did not have such contact.…”
Section: Awareness Of Persons With Disabilitiesmentioning
confidence: 99%
“…However, Eigenbroad and Retish (1988) suggested that the conflict over the role of contact may be related to differences in the quality of contact. A recent study by Levy et al (1992) on Fortune 500 corporate executives supports the importance of prior contact (experience), and the quality ascribed to it. Executives who had had contact with persons with disabilities in the corporate work force expressed more favourable attitudes than executives who had no such prior experience.…”
mentioning
confidence: 95%
“…In recent years there has been an effort to incorporate individuals with developmental disabilities into the work place and to engage them in competitive employment (Levy, Jones-Jessop, Rimmerman, & Levy, 1992). Employing workers labeled as being with mild and moderate intellectual disability in competitive positions not only reduces support and treatment costs of caring for these individuals and allows them to pay taxes (Wehman et al, 1982), but also improves their self-confidence and independence (Brown et al, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation